2021
DOI: 10.3390/su13137328
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Energy and Renewable Energy Policies in Iran

Abstract: Iran, endowed with abundant renewable and non-renewable energy resources, particularly non-renewable resources, faces challenges such as air pollution, climate change and energy security. As a leading exporter and consumer of fossil fuels, it is also attempting to use renewable energy as part of its energy mix toward energy security and sustainability. Due to its favorable geographic characteristics, Iran has diverse and accessible renewable sources, which provide appropriate substitutes to reduce dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 53 publications
0
41
0
1
Order By: Relevance
“…Although Iran is a rich country in terms of both renewable and non-renewable energy sources ( Fadai et al, 2011 ), renewable sources of energy do not play a significant role in the energy supply in this country ( Solaymani, 2021 ). Research shows that Iran is facing several challenges for knowledge creation and diffusion of renewable energy technologies ( Fartash et al, 2021 ), and the post-pandemic era is worse than the pre-pandemic regarding the development of renewable energies in this country ( Ghaboulian Zare et al, 2022 ).…”
Section: Strategy Formulation and Scenario Analysismentioning
confidence: 99%
“…Although Iran is a rich country in terms of both renewable and non-renewable energy sources ( Fadai et al, 2011 ), renewable sources of energy do not play a significant role in the energy supply in this country ( Solaymani, 2021 ). Research shows that Iran is facing several challenges for knowledge creation and diffusion of renewable energy technologies ( Fartash et al, 2021 ), and the post-pandemic era is worse than the pre-pandemic regarding the development of renewable energies in this country ( Ghaboulian Zare et al, 2022 ).…”
Section: Strategy Formulation and Scenario Analysismentioning
confidence: 99%
“…Based on the presented studies, an efficient solar thermal system is economically viable in Iran by upgrading the grid infrastructure and implementing commercial renewable energy systems for buildings as tabulated in Table 1. The government policies for developing renewable energy systems are defined by the ministries of energy and petroleum in which the installed capacity of renewable energies should rise by 5% in 2021 [45]. However, the low cost of energy is the main limitation for this development.…”
Section: Solar Water Heating Systems In Iranmentioning
confidence: 99%
“…They analyzed the future trend of renewable energy in Iran to declare investment opportunities and examined three scenarios for analyzing renewable energy in Iran. Solaymani [16] examined trends in energy demand, policies, and development of renewable energies and the causal relationship between renewable and non-renewable energies and economic growth using two methodologies. His results showed that renewable energy technologies currently do not have a significant and adequate role in the energy supply of Iran and also showed that there was a unidirectional causal relationship between economic growth to renewable and non-renewable energy use.…”
Section: Introductionmentioning
confidence: 99%